2019
DOI: 10.1182/bloodadvances.2019000518
|View full text |Cite
|
Sign up to set email alerts
|

Ring sideroblasts in AML are associated with adverse risk characteristics and have a distinct gene expression pattern

Abstract: Key Points Ring sideroblasts in AML are associated with complex karyotypes and TP53 mutations. Gene expression studies in CD34+ AML cells suggest an altered erythroid differentiation program in AML with ring sideroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Next, we verified whether the observed findings of mutant p53 in HSPC and cell lines were also present in patient AML cells (which have also additional mutations) with and without TP53 mutations. Therefore, we used three large available data sets (Blueprint [14] supplemented with five additional TP53 mutant AML [15], TCGA [16], and BeatAML [17]) and identified the differentially expressed genes between TP53 mut and TP53 wt AMLs for each database. Per data set, we detected differential gene expression between TP53 mut AMLs and TP53 wt AMLs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we verified whether the observed findings of mutant p53 in HSPC and cell lines were also present in patient AML cells (which have also additional mutations) with and without TP53 mutations. Therefore, we used three large available data sets (Blueprint [14] supplemented with five additional TP53 mutant AML [15], TCGA [16], and BeatAML [17]) and identified the differentially expressed genes between TP53 mut and TP53 wt AMLs for each database. Per data set, we detected differential gene expression between TP53 mut AMLs and TP53 wt AMLs.…”
Section: Resultsmentioning
confidence: 99%
“…Also, previous studies had revealed an association between TP53 mutations and erythroid development in leukemia. In acute erythroid leukemia, a high incidence of loss of WT TP53 function is noted [21,25], and the presence of ring sideroblasts in secondary AML is frequently associated with TP53 mutations [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between SF3B1 mutations and the RS phenotype is not as strong as in MDS. RNA sequencing analysis on precursor cells revealed that several heme metabolism-related genes are upregulated in AML-RS cells similarly to SF3B1-mutated MDS, demonstrating the involvement of common downstream effector pathways [53].…”
Section: Sf3b1 In Acute Myeloid Leukemiamentioning
confidence: 98%
“…Ring sideroblasts can also be present in a subset of patients with acute myeloid leukemia (AML), ranging from 5 to 16% [ 141 , 189 ], whereas SF3B1 mutations are infrequent [ 141 , 190 ]. Berger et al studied 126 AML patients with ring sideroblasts ≥1% [ 191 ]. AML-RS subjects were enriched in the ELN adverse risk category with 35% of all cases showing cytogenetic aberrancies.…”
Section: Clonal Sideroblastic Anemiasmentioning
confidence: 99%